Of Motivation and Learning English: A Perspective on EFL Students in Bangladesh - Kabir, SM Akramul (IIUC Studies, 2016)
Motivation and learning tend to be interrelated with each other. Among all other learning variables, motivation is considered the most significant factor in language learning. The More a learner is motivated the more effective learning takes place. Learning a foreign language such as English denotes the preference and zeal of the learner depending on the intensity of motivation. So, in order to help the students to maintain proper strength in English, learning motivation is essential for the teachers in regular teaching procedure. This paper discusses the role of motivation for English language learning in four main sections focusing on EFL students of Bangladesh. Finally, some suggestions are offered to the teachers IIUC Studies Vol.12 December 2015: 139-146